2022
DOI: 10.1167/tvst.11.3.33
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Variant Causality and Severity Using Retinal Pigment Epithelial Cells Derived from Stargardt Disease Patients

Abstract: Purpose Modern molecular genetics has revolutionized gene discovery, genetic diagnoses, and precision medicine yet many patients remain unable to benefit from these advances as disease-causing variants remain elusive for up to half of Mendelian genetic disorders. Patient-derived induced pluripotent stem (iPS) cells and transcriptomics were used to identify the fate of unsolved ABCA4 alleles in patients with Stargardt disease. Methods Multiple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(23 citation statements)
references
References 39 publications
(37 reference statements)
2
21
0
Order By: Relevance
“…43 In comparing patient phenotypes, the higher the missense variant expression, the more deleterious outcomes for the patient, and iPSC studies confirmed this genotype-phenotype correlation in the severity of ABCA4 variants. 38,43 Consistent with STGD1 disease phenotypes, the transcriptomic analysis of the patient iPSC-derived RPE cells, links oxidative and endoplasmic reticulum stress, likely symptoms of reactive responses rather than primary protein alterations due to ABCA4 variants. 38,43 This study highlights the benefits of using iPSC-derived RPE to assess casual variants in difficult to detect genomic regions.…”
Section: Stargardt Diseasementioning
confidence: 78%
See 4 more Smart Citations
“…43 In comparing patient phenotypes, the higher the missense variant expression, the more deleterious outcomes for the patient, and iPSC studies confirmed this genotype-phenotype correlation in the severity of ABCA4 variants. 38,43 Consistent with STGD1 disease phenotypes, the transcriptomic analysis of the patient iPSC-derived RPE cells, links oxidative and endoplasmic reticulum stress, likely symptoms of reactive responses rather than primary protein alterations due to ABCA4 variants. 38,43 This study highlights the benefits of using iPSC-derived RPE to assess casual variants in difficult to detect genomic regions.…”
Section: Stargardt Diseasementioning
confidence: 78%
“…38,43 Consistent with STGD1 disease phenotypes, the transcriptomic analysis of the patient iPSC-derived RPE cells, links oxidative and endoplasmic reticulum stress, likely symptoms of reactive responses rather than primary protein alterations due to ABCA4 variants. 38,43 This study highlights the benefits of using iPSC-derived RPE to assess casual variants in difficult to detect genomic regions.…”
Section: Stargardt Diseasementioning
confidence: 84%
See 3 more Smart Citations